Model algorithmic control: |an application to DC motor speed control - Özperk, Tuna. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1985., 1985)
The growth of digital technology in the last few years has represented a challenge to automatic control research workers. The increasing use of digital minicomputers has considerably helped the industrial implementation of algorithmic types of control. For this type of control to be practical and efficient,it is imperative for the controller to have access to fast digital computing facilities with fast memory access and substential information storage capacity. In this thesis a new method of digital process control which is applied 'to a number of industrial processes ranging from power plants to glass furnaces,is described.This new control method is called Model Algorithmic Control or equivalently Model Predictive Heuristic Control.A mathematical framework for the analysis of Model Algorithmic Control is developed and the operations of the main components of the control structure are described. The Model. Algorithmic Control strategy relies on three principles: i. the plant is represented by its impuls response which will be used on-line by the computer for prediction, ii.the behavior of the closed-loop system is prescribed by means of reference trajectory initiated on the actual output, iii. the control variables are computed in a heuristic way. Future inputs are computed in such a way that when applied to the internal predictive model,it induces outputs as close as possible to the desired reference trajectory. In this thesis,the Model Algorithmic Control is applied to dc motor speed control. Control algorithm is evaluated by a Z-80 based microcomputer, and the output of microcomputer is applied to a fully controlled thyristor converter unit as a speed reference input through a digital to analog converter. The actual speed of the motor is inputed to the microcomputer by means of a tachogenerator through an analog to digital converter. The application of Model Algorithmic Control to dc motor speed control is devided in two parts.In the first part of the application, the set speed is constant, the algorithm causes the speed of the motor to reach that constant speed with a time constant similar to the reference trajectory. The time responses of motor output speed are observed for different time constants.In the second part, the set speed is time varying. In this part the set speed is changed as a linear ramp,the tracking behavior of the dc motor output speed is observed. In chapter one, the methods for the speed control of a separately excited direct current motor are described and compared with each others. Consequently,the equations determining the dynamical behavior of the motor and the transfer function of the motor are derived. In chapter two, solid state dc motor drives are described and the operation of a three phase full converter is explained in general terms.The features of the thyristor unit used in the realization of the control is then presented. In chapter three, a mathematical framework for the analysis of Model Algorithmic Control is developed and. the operations of the main components of the control structure are described. The equations to calculate the optimum inputs are derived. In chapter four, the model which will be used in the algorithm is introduced. The discrete impuls response of the system is found and the overall set up for closed-loop control is given.Additionally the software developed is presented and explained. In chapter five, the stability analysis of the Model Algorithmic Controlis developed. The robustness of the system to the parameter changes is discussed.Finally the effects of the constraints on input sequence to system stability are discussed, and the experimental results are presented.
Keywords: Electric motors, Direct current.; Control theory.; Algorithms.